Impact of Risk Factors for Specific Causes of Death in the First and Subsequent Years of Antiretroviral Therapy Among HIV-Infected Patients. (24th April 2014) - Ingle, Suzanne M.; May, Margaret T.; Gill, M. John; Mugavero, Michael J.; Lewden, Charlotte; Abgrall, Sophie; Fätkenheuer, Gerd; Reiss, Peter; Saag, Michael S.; Manzardo, Christian; Grabar, Sophie; Bruyand, Mathias; et al.
Abstract : Among HIV-infected patients who initiated antiretroviral therapy (ART), patterns of cause-specific death varied by ART duration and were strongly related to age, sex, and transmission risk group. Deaths from non-AIDS malignancies were much more frequent than those from cardiovascular disease. Abstract : Background.  Patterns of cause-specific mortality in individuals infected with human immunodeficiency virus type 1 (HIV-1) are changing dramatically in the era of antiretroviral therapy (ART). Methods.  Sixteen cohorts from Europe and North America contributed data on adult patients followed from the start of ART. Procedures for coding causes of death were standardized. Estimated hazard ratios (HRs) were adjusted for transmission risk group, sex, age, year of ART initiation, baseline CD4 count, viral load, and AIDS status, before and after the first year of ART. Results.  A total of 4237 of 65 121 (6.5%) patients died (median, 4.5 years follow-up). Rates of AIDS death decreased substantially with time since starting ART, but mortality from non-AIDS malignancy increased (rate ratio, 1.04 per year; 95% confidence interval [CI], 1.0–1.1). Higher mortality in men than women during the first year of ART was mostly due to non-AIDS malignancy and liver-related deaths. Associations with age were strongest for cardiovascular disease, heart/vascular, and malignancy deaths. Patients with presumed transmission through injection drug use had higher rates of all causes of death, particularly for liver-related causes (HRs compared with men who have sex with men: 18.1 [95% CI, 6.2–52.7] during the first year of ART and 9.1 [95% CI, 5.8–14.2] thereafter). There was a persistent role of CD4 count at baseline and at 12 months in predicting AIDS, non-AIDS infection, and non-AIDS malignancy deaths. Lack of viral suppression on ART was associated with AIDS, non-AIDS infection, and other causes of death. Conclusions.  Better understanding of patterns of and risk factors for cause-specific mortality in the ART era can aid in development of appropriate care for HIV-infected individuals and inform guidelines for risk factor management.